Photopatternable and Rewritable Epoxy‐Anhydride Vitrimers. Issue 2 (29th September 2020) - Giebler, Michael; Alabiso, Walter; Wieser, Viktoria; Radl, Simone; Schlögl, Sandra
Abstract: The present work highlights a new approach to write, erase, and rewrite micropatterns into the same region of covalent adaptable polymer networks. Thermal curing of an epoxy‐terminated o ‐nitrobenzyl ester ( o ‐NBE) derivative with hexahydrophthalic anhydride in the presence of 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene yields a dynamic covalent network, whose solubility is locally controlled by irradiation with ultraviolet (UV) light. The photolysis of the o ‐NBE chromophores enables a well‐defined cleavage of the epoxy‐anhydride network, and the formation of soluble photolysis products is confirmed by sol‐gel analysis. The photo‐induced change in solubility is exploited to inscribe micropatterns by photolithographic techniques and after development in an organic solvent positive tone structures with a feature size of 20 µm are obtained. Due to the thermo‐activated exchange reactions of the hydroxyl ester links and the related macroscopic reflow, the polymer patterns are fully erased at temperatures well above the topological freezing transition of the vitrimer network. The regenerated film has a smooth surface topology and can be reused to inscribe new micropatterns via mask lithography. Abstract : An epoxy‐anhydride vitrimer with photolabile ortho‐nitrobenzyl ester links is synthetized. Solubility of the vitrimer is conveniently controlled by irradiation with ultraviolet light. Positive‐tone microstructures with feature sizes of 20 µm are inscribed by photolithography and thermally erased via catalyzed transesterifications of the covalent adaptable network. Thermo‐activated reflow facilitates smooth surfaces on which new microstructures are rewritten in the same region.